Primary posterior mediastinal Burkitt lymphoma - Mutlu, Mehmet; Kurucu, Nilgün; Sarıhan, Haluk; Ahmetoğlu, Ali; Yıldız, Kadriye (The Turkish Journal of Pediatrics, 2011)
A 14-year-old boy admitted to our clinic with a 20-day history of fever, cough and respiratory distress. Mediastinal enlargement was observed on chest radiograph. Computed tomography of the chest demonstrated a large posterior mediastinal mass. The histopathological examination of the mass revealed Burkitt's lymphoma. We report this case because primary posterior mediastinal involvement in Burkitt lymphoma is extremely rare in childhood.